Targeting acetyl-CoA carboxylase 1 for cancer therapy - Yu, Yong; Nie, Qingzhu; Wang, Ziyi; Di, Yu; Chen, Xiaolong; Ren, Kaiming (Frontiers in Pharmacology, 2023)
Metabolic adaptation is an emerging hallmark of tumors. De novo fatty acid synthesis is an important metabolic process to produce metabolic intermediates for energy storage, biosynthesis of membrane lipids and generation of signaling molecules. Acetyl-CoA carboxylase1 (ACC1) is a critical enzyme in the fatty acid synthesis, which carboxylates acetyl-CoA carboxylic acid to form malonyl-CoA. The role of ACC1 in fatty acid synthesis makes it a promising therapeutic target for various metabolic diseases such as nonalcoholic fatty liver disease, obesity and diabetes. Tumors have a high energy flow and a strong dependence on fatty acid synthesis. Thus, ACC inhibition has become a potential choice for anti-tumor therapy. In this review, we first introduced the structure and expression pattern of ACC1. We also discussed the molecular mechanisms of ACC1 in the initiation and progression of various cancer types. Furthermore, ACC1 inhibitors has also been discussed. Collectively, we summarized the interplay between ACC1 and tumorigenesis, indicating ACC1 as a promising therapeutic target for tumor management.